Information technology and agricultural engineering - Sambath, Sabo; Zhu, Egui (Advances in Intelligent and Soft Computing, 2012)
This volume comprises the papers from 2011 International Conference on Information Technology and Agricultural Engineering (ICITAE 2011).  2011 International Conference on Information Technology and Agricultural Engineering (ICITAE 2011) has been held in Sanya, China, December 1-2, 2011. All the papers have been peer reviewed by the selected experts. These papers represent the latest development in the field of materials manufacturing technology, spanning from the fundamentals to new technologies and applications. Specially, these papers cover the topics of Information Technology and Agricultural Engineering. This book provides a greatly valuable reference for researchers in the field of Information Technology and Agricultural Engineering who wish to further understand the underlying mechanisms and create innovative and practical techniques, systems and processes. It should also be particularly useful for engineers in information technology and agriculture who are responsible for the efficient and effective operations.